TUBERCULOSIS WITH CONCURRENT HIV INFECTION IN RUSSIA: STATISTICS AND CORRELATIONS - E. B. Tsybikova; V. V. Punga; L. I. Rusakova (Туберкулез и болезни лёгких)
The objective of the study is to analyze TB/HIV co-infection situation in the regions of RF and to identify correlated epidemiological rates.Subjects and methods. The data from Rosstat Forms no. 61, 8 and 33 were used as well as Rosstat data on the number of population for 2017.The data reflecting the structure of the patients with TB/HIV co-infection were obtained from Rosstat Form no. 61 for 2017.In order to define correlations between the rates characterizing the population of tuberculosis patients and patients with TB/HIV co-infection, the correlation analysis was performed (the standard tools of Statistica software).Results of the study. In Russia, TB/HIV co-infection was not equally prevalent and it was the highest in 35 regions of Russia. According to the results of correlation analysis, in 37 RF regions with a low level of TB/HIV co-infection (< 7% of the total number of tuberculosis patients), tuberculosis mortality during the 1st year of follow-up depended on the prevalence of multiple drug resistant tuberculosis (MDR TB) among all tuberculosis patients. In 48 Russian regions with a high level of TB/HIV co-infection (≥ 7% of the total number of tuberculosis patients), the prevalence of MDR TB and mortality in the patients within the 1st year of follow up directly depended on the prevalence of this co-infection. In 16 Russian regions, where the portion of new cases with concurrent MDR TB made from 23 to 60%, the risk of lethal outcome was the highest. The co-morbidity with hepatitis was observed in 42% of new cases of co-infection and in 43% of all those being followed-up.